(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Objective: The objective of this study is to review published cost-utility analyses of vaccination strategies in eight European countries and to assess whether there are differences in cost-effectiveness terms among countries and vaccinations. Methods: A systematic search of the literature was conducted using the National Health Service Economic Evaluation Database and the PubMed database. Cost-utility analyses of any type of vaccination that used quality-adjusted life years (QALYs) as measure of benefit and conducted in Belgium, France, Germany, Italy, Spain, Sweden, the Netherlands or the UK were included. Results: A total of 94 studies were identified. As a result of our search methodology, the vast majority of studies were conducted in the Netherlands or UK (33 and 30 studies, respectively). The most frequent vaccination types were against Human papillomavirus (HPV) with 23 studies, followed by vaccination against pneumococcal infections (19 studies). The analysed vaccinations were generally cost-effective but with high variability. Considering an incremental cost effectiveness ratio (ICER) of 40,000€/QALY, we noticed that the following vaccinations studies are below this threshold, i.e. all varicella and influenza (with one outlier) studies, 90% of the studies for HPV and 75% of the studies for pneumococcal vaccinations. Rotavirus vaccination was considered as not cost-effective, with only 30% of studies below the threshold of 40,000€/QALY. There was no clear trend for vaccinations being more cost-effective in some countries. Conclusions: The published literature has shown that vaccination strategies are generally cost-effective in European countries. High heterogeneity in the results among studies and countries was found.